2022
DOI: 10.4103/jllr.jllr_1_22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frame and Fixation Factors on the Incidence of Pin Site Infections in Circular External Fixation of the Tibia

Abstract: Introduction: Pin site infections (PSIs) are frequent complications encountered with the use of circular external fixators. PSIs range in severity, and the numerous factors have been suggested to affect the incidence. We aim to perform a systematic review of all comparative studies including circular external fixation applied to the tibia diaphysis in adult patients and to explore frame and fixation factors that may be associated with the development of PSI. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a meta-analysis, Arveladze et al found limited evidence for the influence of the material and coating on the incidence of pin-site infections 61 . Laubscher et al identified a lack of comparative studies in the literature and concluded that further studies were necessary to determine the effect of frame and fixation factors on the incidence of pin-site infection 62 . Ban et al found inconclusive results in a review of studies focused on the relationship between the wire application technique and the incidence of pin-site infection 63 .…”
Section: Pin-site Infectionmentioning
confidence: 99%
“…In a meta-analysis, Arveladze et al found limited evidence for the influence of the material and coating on the incidence of pin-site infections 61 . Laubscher et al identified a lack of comparative studies in the literature and concluded that further studies were necessary to determine the effect of frame and fixation factors on the incidence of pin-site infection 62 . Ban et al found inconclusive results in a review of studies focused on the relationship between the wire application technique and the incidence of pin-site infection 63 .…”
Section: Pin-site Infectionmentioning
confidence: 99%